Clinical efficacy comparison of sclerosing embolization with 3% polidocanol and the microsurgical subinguinal varicocelectomy in primary varicocele patients. (8th July 2022) - Feng, Rui; Jiang, Jingsong; Cheng, Dexin; Lu, Kaiping
Abstract: Varicocele is a more common male genitourinary system disease with sperm quality dysfunction or discomfort. This study was aimed to compare the clinical efficacy of sclerosing embolization with 3% polidocanol and the microsurgical subinguinal varicocelectomy in treating primary varicocele. Total of 59 patients with primary varicocele receiving a 3‐month postoperative follow‐up were included to analyse their biochemical parameters and clinical outcomes, including the operative time, hospitalization time, postoperative recurrence rates, and complication rate. Nineteen patients were treated with sclerosing embolization with 3% polidocanol (SE group), while 40 patients were treated with microsurgical subinguinal varicocelectomy (MSV group). For the SE group, 17 patients were treated on the left side, and two patients have treated on both without recurrences and complications during the follow‐up period. For the MSV group, three patients were treated bilaterally, and 36 patients were treated separately on the left side with a total 5% recurrence rate and 10% complication rate. The duration of surgery and the hospitalization time of the SE group (46.2 ± 9.79 min and 2.53 ± 0.90 days, respectively) are significantly lower than MSV group (100.5 ± 13.76 min and 3.6 ± 1.58 days, respectively), p  < 0.05. The total sperm count at 3 months was significantly higher in the SE group than in the MSV group ( p  < 0.05). In summary, sclerosing embolization is more effective for varicocele in improving sperm quality, shortening recovery time, and reducing recurrence rates and complications.